Effects of pH and fluoride concentration of dentifrices on fluoride levels in saliva, biofilm, and biofilm fluid in vivo - Kondo, Karina Yuri [UNESP]; Buzalaf, Marília Afonso Rabelo; Manarelli, Michele Mauricio [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Pessan, Juliano Pelim [UNESP] (Springer, 2015)
Acidic dentifrices have been shown to be more effective than neutral ones against dental caries using in vitro, in situ, and clinical protocols. Given the scarcity of studies assessing intraoral fluoride (F) retention after using such formulations, the present study evaluated the influence of pH and F concentration of dentifrices on F uptake by saliva, biofilm, and biofilm fluid. Volunteers (n = 22) were randomly assigned to dentifrices containing 0 (placebo), 550 (LFD, low-fluoride dentifrice), and 1100 ppm F (CD, conventional dentifrice) at pH 4.5 and 7.0 and brushed their teeth 3 times/day following a double-blind, crossover protocol. Saliva and biofilm samples were collected after 7 days of using the dentifrices, 1 and approximately 12 h after last brushing. F and calcium (Ca) analyses were performed with the inverted electrode after buffering with TISAB III and the Arsenazo III method, respectively. Data were analyzed by 3-way ANOVA, Tukey's HSD test, and Pearson's correlation coefficient (p < 0.05). F concentrations in biofilm fluid and whole biofilm 1 h after brushing with acidic F-toothpastes were higher than those related to neutral counterparts, although the differences were small and not significant; no increases were observed in salivary F concentrations influenced by dentifrice pH. Moreover, no definite trend was observed for Ca concentrations in these compartments. Dentifrice pH had some influence on F uptake by the biofilm fluid, having lesser or no impact on F uptake by the biofilm and saliva, respectively. Toothbrushing with acidic toothpastes leads to slight increases in F concentrations in the biofilm fluid when compared to neutral formulations, which may contribute to the higher anticaries effect of acidic formulations.
Keywords: Fluoride; Dentifrices; Dental plaque; Saliva; Biofilm; Biofilm fluid